Pengaruh Layanan Informasi Karir dengan Pendekatan Trait And Factor terhadap Pengambilan Keputusan Karir pada Mahasiswa UIN Raden Fatah Palembang: Penelitian - Zhila Jannati; Hartika Utami Fitri; Hesti Trianjani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of career information services with the Trait and Factor approach on the career decision-making ability of students at UIN Raden Fatah Palembang. The study used a quantitative approach with an experimental pretest-posttest control group design method. The research sample consisted of 77 students selected using the Single-Stage Cluster Sampling technique, consisting of 39 students in the experimental group and 38 students in the control group. Data were collected through a career decision-making questionnaire and analyzed using the Independent Sample t-Test with the help of the SPSS version 25 program. The results showed an increase in career decision-making ability in the experimental group compared to the control group. The average (mean) value of the experimental group increased from 46 in the pretest to 131 in the posttest, while the control group increased from 46 to 119. The t-test results showed a Sig. (2-tailed) value of 0.518 (> 0.05) which indicated that there was no statistically significant difference between the two groups after treatment. However, the increase in the average score of the experimental group indicates that career information services using the Trait and Factor approach still have a positive influence on improving students' career decision-making abilities. This finding emphasizes the importance of implementing career information services in Islamic guidance and counseling activities to help students understand their potential and the world of work more rationally and realistically, so they can determine career choices that align with their personal values, interests, and abilities.